Physical properties of molecular clouds at 2 parsec resolution in the low-metallicity dwarf galaxy NGC 6822 and the Milky Way - Schruba, Andreas; Kruijssen, Diederik; Bigiel, Frank (Arxiv, 2017)
We present the ALMA survey of CO(2-1) emission from the 1/5 solar metallicity, Local Group dwarf galaxy NGC 6822. We achieve high (0.9 arcsec ~ 2 pc) spatial resolution while covering large area: four 250 pc x 250 pc regions that encompass ~2/3 of NGC 6822's star formation. In these regions, we resolve ~150 compact CO clumps that have small radii (~2-3 pc), narrow line width (~1 km/s), and low filling factor across the galaxy. This is consistent with other recent studies of low metallicity galaxies, but here shown with a 15 times larger sample. At parsec scales, CO emission correlates with 8 micron emission better than with 24 micron emission and anti-correlates with Halpha, so that PAH emission may be an effective tracer of molecular gas at low metallicity. The properties of the CO clumps resemble those of similar-size structures in Galactic clouds except of slightly lower surface brightness and CO-to-H2 ratio ~1-2 times the Galactic value. The clumps exist inside larger atomic-molecular complexes with masses typical for giant molecular cloud. Using dust to trace H2 for the entire complex, we find CO-to-H2 to be ~20-25 times the Galactic value, but with strong dependence on spatial scale and variations between complexes that may track their evolutionary state. The H2-to-HI ratio is low globally and only mildly above unity within the complexes. The SFR-to-H2 ratio is ~3-5 times higher in the complexes than in massive disk galaxies, but after accounting for the bias from targeting star-forming regions, we conclude that the global molecular gas depletion time may be as long as in massive disk galaxies.